Effects of circumferential and axial grooves on the nonlinear oscillations of the full floating ring bearing supported turbocharger rotor. (May 2019) - Zhang, Congcong; Men, Rixiu; He, Hong; Chen, Wei
It is seen that with the reduction in land areas owing to the floating-rings featured grooves, there is reduction in the load capacities and bearing torques of the oil-films, which have an influence on the nonlinear oscillations of turbocharger rotors. In the present paper, the impact of the reduced load capacities and bearing torques caused by circumferential or/and axial grooves in full-floating-ring bearings on the nonlinear oscillations of turbocharger rotors is investigated. The numerical solution of the Reynolds equation for full-floating-ring bearings with grooves by means of a finite difference or finite element approach imposes a prohibitive simulation times, sine in every time-integration step a direct discretization of the Reynolds equation has to be solved simultaneously with the rotor model. To be able to perform transient simulations, a computationally efficient full-floating-ring bearing model is mandatory. To surmount this problem, a very time-efficient but rather precise method is proposed. The major point of the proposed method is the manipulation of the Reynolds equation to allow a speed parameter varying within (−1, +1) to reflect the relative weights of the journal and floating ring's rotation and squeezing effects. Given the diameter-to-length ratio of each fluid film, groove widths, and boundary conditions, the fluid force databases can be easily established by the finite difference method. During the transient response analysis, the required fluid forces and bearing torques from each film can be evaluated by interpolation using the existent forces and torques of the closest points in the databases. Using transient simulations with the proposed method, the effect of circumferential or/and axial grooves in full-floating-ring bearings on the amplitudes and frequencies of the nonlinear oscillations of turbocharger rotors is qualitatively investigated. It is shown that the reduction of the load capacities and bearing torques due to grooves exert a large influence on the nonlinear rotor oscillations.